2016
DOI: 10.1021/acs.biochem.6b00829
|View full text |Cite
|
Sign up to set email alerts
|

High-Affinity Binding of Monomeric but Not Oligomeric Amyloid-β to Ganglioside GM1 Containing Nanodiscs

Abstract: The interaction of the amyloid-β protein (Aβ) with neuronal cell membranes plays a crucial role in Alzheimer's disease. Aβ undergoes structural changes upon binding to ganglioside GM1 containing membranes leading to altered molecular characteristics of the protein. The physiological role of the Aβ interaction with the ganglioside GM1 is still unclear. In order to further elucidate the molecular requirements of Aβ membrane binding, we tested different nanodiscs varying in their lipid composition, regarding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 66 publications
2
19
0
Order By: Relevance
“…Notably, NDs have been used before to study the effect of calcium ions on the membrane interaction of αS 32 , as well as lipid and monomer specificity of the Alzheimer-associated Aβ peptide 33 . In general, NDs are very homogeneous, stable in a wide buffer range 34 , and allow the preparations of well-defined lipid mixtures with an accurate estimate of the bilayer size 35 , charge 36 , and lipid molarity 37 .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, NDs have been used before to study the effect of calcium ions on the membrane interaction of αS 32 , as well as lipid and monomer specificity of the Alzheimer-associated Aβ peptide 33 . In general, NDs are very homogeneous, stable in a wide buffer range 34 , and allow the preparations of well-defined lipid mixtures with an accurate estimate of the bilayer size 35 , charge 36 , and lipid molarity 37 .…”
Section: Introductionmentioning
confidence: 99%
“…. Just as Aβ binds to the GM1 ganglioside in the membrane to become the seed for amyloid formation, we propose that TTR G47R binds to the basement membranes to accelerate ATTR accumulation in the subarachnoid area. ATTR deposition spreads in the tissue but is retained and degraded by the ubiquitin proteasome system of glial cells on the brain surface.…”
Section: Discussionmentioning
confidence: 93%
“…Amyloidogenic proteins such as Aβ protein and TTR variants are misfolded after translation, causing them to self‐aggregate through mechanisms that are poorly understood in vivo. It is known that in the presence of membranes, amyloidogenic proteins produce amyloids more easily due to interactions with biological membranes . The basement membrane is an extracellular matrix, which covers the basal aspect of most cells and contributes to various functions, including establishment of the tissue structure support and clearance of Aβ .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6,7 Recent studies have further shown gangliosides (GM), sphingomyelin (SM) and cholesterol to be the major modulators of Aβ oligomerization. 8,9 Although, recent studies proposed the catalytic activities of lipidmembrane on Aβ deposition and aggregation, the exact function of these lipids is not yet fully understood. 9,10 Herein, we have investigated the roles of membrane composition in modulating Aβ's aggregation using polymethacrylate (PMA) copolymer encased lipid-nanodiscs in an attempt to trap and characterize structure and toxicity of Aβ intermediates.…”
mentioning
confidence: 99%